Investigation of Stress Status in the Micro-Space of Surface and Subsurface Layer - Czan, Andrej; Sajgalik, Michal; Zauskova, Lucia; Cep, Robert; Rysava, Zdenka; Sordi, Vitor Luiz (Communications - Scientific letters of the University of Zilina, 2017)
One of main issues when evaluating or analysing quality and functional properties of work-piece is identification of status of residual stress. Every treatment or machining process generates residual stress in the surface and subsurface layers of the material structure. The residual stress has a large influence on the functional properties of the components. The article is focused on the method of triaxial measurement of residual stress after machining the surface of sample by high feed milling technology. Significance of triaxial measuring is the capability of measuring in different angles so it is possible to acquire stress tensor containing normal and shear stress components acting in the spot of measuring, using a Cartesian coordinate system.